Bag-1 stimulates Bad phosphorylation through activation of Akt and Raf kinases to mediate cell survival in breast cancer - Kizilboga, Tugba (BMC Cancer, 2019)
BACKGROUND: Bag-1 (Bcl-2-associated athanogene) is a multifunctional anti-apoptotic protein frequently overexpressed in cancer. Bag-1 interacts with a variety of cellular targets including Hsp70/Hsc70 chaperones, Bcl-2, nuclear hormone receptors, Akt and Raf kinases. In this study, we investigated in detail the effects of Bag-1 on major cell survival pathways associated with breast cancer. METHODS: Using immunoblot analysis, we examined Bag-1 expression profiles in tumor and normal tissues of breast cancer patients with different receptor status. We investigated the effects of Bag-1 on cell proliferation, apoptosis, Akt and Raf kinase pathways, and Bad phosphorylation by implementing ectopic expression or knockdown of Bag-1 in MCF-7, BT-474, MDA-MB-231 and MCF-10A breast cell lines. We also tested these in tumor and normal tissues from breast cancer patients. We investigated the interactions between Bag-1, Akt and Raf kinases in cell lines and tumor tissues by co-immunoprecipitation, and their subcellular localization by immunocytochemistry and immunohistochemistry. RESULTS: We observed that Bag-1 is overexpressed in breast tumors in all molecular subtypes, i.e., regardless of their ER, PR and Her2 expression profile. Ectopic expression of Bag-1 in breast cancer cell lines results in the activation of B-Raf, C-Raf and Akt kinases, which are also upregulated in breast tumors. Bag-1 forms complexes with B-Raf, C-Raf and Akt in breast cancer cells, enhancing their phosphorylation and activation, and ultimately leading to phosphorylation of the pro-apoptotic Bad protein at Ser112 and Ser136. This causes Bad’s re-localization to the nucleus, and inhibits apoptosis in favor of cell survival. CONCLUSIONS: Overall, Bad inhibition by Bag-1 through activation of Raf and Akt kinases is an effective survival and growth strategy exploited by breast cancer cells. Therefore, targeting the molecular interactions between Bag-1 and these kinases might prove an effective anticancer therapy.